Design and Development of Effective Multi-Level Cache Memory Model - Udoka, Eze Val Hyginus; Eze, Martin Chinweokwu; Edozie, Enerst; Eze, Esther Chidinma (International Journal of Recent Technology and Applied Science (IJORTAS), 2023)
An algorithm to determine the effectiveness and efficiency of a multi-level cache was developed in this paper. The developed model was used to test the efficiency rate, the relationships and the performance output level of a computer concerning the cache properties. This research paper showed that the level of cache and access time increases with the absolute hit rate but decreases with the relative hit rate. The number of cache levels varies directly with absolute access time and inversely with relative access time. The level one cache with set associativity of one has the highest access time and as the associativity and cache levels increase the memory access time decreases. The increase in the number of set associativity leads to an increase in cache performance and as well increases the performance speed of a computer.